Skills needed by accounting practitioners in the digital era - ‘Adilah, Md Rodzi (2019)
The purpose of this study is to identify what soft skills and IT/digital skills that student perceived and lecturers believed as being important in the accounting career success. The data for this study were collected by using qualitative and quantitative method. Qualitative data collected from accounting lecturers through interview session and quantitative data collected from accounting students of UUM through questionnaire. The result of this study shows that student perceived that interpersonal and teamwork were the most important soft skills while cyber security and accounting system for IT/digital skills. Different with accounting lecturers, they believed that communication and critical thinking skills were important for soft skills while spread sheet and accounting software for IT/digital skills. This study increases the awareness among student on the skills that they should possess with in order for them to enter the job market easily. The limitations in this study is it focused solely on accounting students and academician from the UUM so the results are inadequate to draw conclusions for all accounting students throughout Malaysia. For the future research, researcher should use a larger sample or they could include students from private as well as public universities from various part of the country to participate in the study.